TINJAUAN VARIABEL-VARIABEL CAMEL TERHADAP PERTUMBUHAN LABA USAHA PADA BANK UMUM SWASTA NASIONAL DEVISA - Eka Dyah Setyaningsih (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The health of banks is closely related to the fulfillment of regulations on compliance with Bank Indonesia. Bank is healthy through the bank's financial statements which can exercise some control over aspects of the capital, assets, profitability, liquidity management and aspects. Hence the analysis of financial statements can use variables CAMEL (Capital, Assets, Management, Earnings, Liquidity) to help business people, government and other users of financial statements to assess the financial condition of the banking company, the company is no exception. Healthy banks is the ability to conduct normal banking operations and is able to meet all of their obligations well in ways that are consistent with the prevailing banking regulations. In order to see the health of banks, this study aims to review the variables that influence camel anything and had no effect in increasing the profits of a bank. The method used multiple linear regression method through data processing SPSS version 20. There are six variables camel namely CAR, ROA, LDR, NIM, ROA and NPL from the influential six is ROA, NIM and NPL her and that no effect is CAR, LDR and ROA during the period 2011 to 2016 in the national private commercial bank foreign exchange. Keywords : CAMEL, Operating Profit